Influence of social support on the social adaptive behaviors of children with acute leukemia in China: the mediating role of family functioning - Shen Yuqing; Mo Lin; Yu Lu; Chen ZeFang; Liu Tao; Zeng Yan; Sabika (BMC Pediatrics)
Abstract Background Children with acute leukaemia often have adverse social adaptive behaviors during treatment, and good social support and family function are considered to be important protection factors. However, little is known about the interaction mechanism of social adaptive behaviors, social support and family function in children with acute leukaemia. This study aimed to explore the mediating role of family function in social support and social adaptive behaviors of children with acute leukemia in China. Methods From August to December 2022, face-to-face data collection was conducted using convenience sampling in the Blood Department of a 3 A Children’s Hospital in Chongqing, China. A total of 202 caregivers of children with acute leukemia participated in the questionnaire. Children’s Adaptive Behavior Scale, family function scale and social support scale were used for evaluation. AMOS 26.0 structural equation modelling method was adopted, and Pearson correlation analysis and deviation-corrected centile Bootstrap method were adopted for analysis. Results Among the 202 participants, 22.77% (46/202) of the children with acute leukaemia showed adverse social adaptive behaviors. Social support, family functioning and social adaptive behaviors demonstrated significant correlations(r = 0.318、-0.392,p < 0.05). It is worth noting that family functioning has a full mediating effect on social support and social adaptive behaviors. Conclusions The evidence provided by this study indicates that social support can positively predict social adaptive behaviors, family functioning can negatively predict social adaptive behaviors, and family functioning mediates the relationship between social support and social adaptive behaviors.This study attributes to the development of precise interventions for caregivers for socially adapted behaviours in children with acute leukaemia and has important implications for policy development to improve the social adaptation of children with leukaemia.